2007
DOI: 10.1038/nature05918
|View full text |Cite
|
Sign up to set email alerts
|

Stability and flexibility of epigenetic gene regulation in mammalian development

Abstract: During development, cells start in a pluripotent state, from which they can differentiate into many cell types, and progressively develop a narrower potential. Their gene-expression programmes become more defined, restricted and, potentially, 'locked in'. Pluripotent stem cells express genes that encode a set of core transcription factors, while genes that are required later in development are repressed by histone marks, which confer short-term, and therefore flexible, epigenetic silencing. By contrast, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
1,327
1
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,772 publications
(1,368 citation statements)
references
References 66 publications
18
1,327
1
22
Order By: Relevance
“…Fewer than 300 genes (approximately 5% of the genes examined) were enriched in all three populations and less than 15% of the genes were enriched in both the neural and hematopoietic cell populations (Ramalho-Santos, 2002;Ivanova et al, 2002). Importantly, their gene expression profiles are not only radically different, but the genes themselves are differentially modified by highly complex combinations of epigenetic modifications (DNA methylation and histone modification), which lead to major changes in chromatin structure Reik, 2007). As a result, the expression of genes in a given lineage is subject to multiple layers of regulation.…”
Section: Full Transdifferentiation or Dedifferentiation Into Cells Ofmentioning
confidence: 99%
“…Fewer than 300 genes (approximately 5% of the genes examined) were enriched in all three populations and less than 15% of the genes were enriched in both the neural and hematopoietic cell populations (Ramalho-Santos, 2002;Ivanova et al, 2002). Importantly, their gene expression profiles are not only radically different, but the genes themselves are differentially modified by highly complex combinations of epigenetic modifications (DNA methylation and histone modification), which lead to major changes in chromatin structure Reik, 2007). As a result, the expression of genes in a given lineage is subject to multiple layers of regulation.…”
Section: Full Transdifferentiation or Dedifferentiation Into Cells Ofmentioning
confidence: 99%
“…Importantly, these processes are conducted entirely by multiple cellular interactions and are believed to be programmed in genomic sequences at various rates. However, epigenetic regulation may also be involved, since epigenetic control of gene expression appears to be an important aspect of general embryonic development as well as the differentiation processes of somatic cells (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…DNA methylation consists of the addition of a methyl group to the 5Ј cytosine in a CpG dinucleotide, which favors genomic integrity and ensures proper regulation of gene expression, largely contributing to gene silencing (3). The important roles of DNA methylation in X chromosome inactivation, genomic imprinting, as well as early embryonic development have been clearly delineated (4,5). Indeed, a recent report of a comprehensive analysis of embryonic stem cells subjected to neurogenesis indicated that CpG methylation at a specific locus may have an important function in regulating the lineage commitment of progenitor cells (7,8).…”
mentioning
confidence: 99%
“…In the context of developmental biology, signaling pathway connect to the core transcriptional regulatory network to affect the epigenome of a developing cell through interactions with the epigenetic machinery (Mohammad and Baylin 2010). Therefore, beyond transcription factor-based and signaling pathwaybased regulatory network analysis, a current research direction is the study of epigenomic regulation of the chromatin landscape during cellular development (Reik 2007). Maintaining the proper chromatin structure is critical to control gene expression.…”
Section: Systems Biology Of Developmental Gene Regulationmentioning
confidence: 99%